Impact of lenalidomide on collected hematopoietic myeloid and erythroid progenitors: peripheral stem cell collection may not be affected. Issue 9 (29th July 2019) - Dosani, Talib; Covut, Fahrettin; Pinto, Raisa; Kim, Byung-Gyu; Ali, Naveed; Beck, Rose; Maitta, Robert; Downes, Katharine; Fox, Robert; Reese, Jane; de Lima, Marcos; Malek, Ehsan
Abstract: Lenalidomide (LEN) is commonly used as part of induction therapy in transplant-eligible patients with multiple myeloma. However, LEN use is associated with increased chance of peripheral blood stem cell (PBSC) collection failure. This has led to early collection in patients receiving induction with LEN-containing regimens, and the use of mobilization agents such as plerixafor. Despite potential significant clinical implications, the impact of LEN on autograft composition is unclear. We examined the effect of LEN exposure on hematopoietic progenitors in collected grafts of 94 patients who underwent autologous stem cell transplantation (HSCT) at our institution. LEN exposure resulted in lower myeloid and erythroid progenitors in collected grafts, but this effect was not seen in patients who received plerixafor-based mobilization. Exposure to LEN did not affect PBSC collection, possibly due to high plerixafor use in our cohort (70%). LEN changes the composition of PBSC grafts; the clinical implication of this finding is unknown.